Characterization of Human Colorectal Cancer MDR1/P-gp Fab Antibody - Xuemei Zhang; Gary Guishan Xiao; Ying Gao (The Scientific World Journal)
In this study, the peptide sized 21 kDa covering P-gp transmembrane region was first prepared for generating a novel mouse monoclonal antibody Fab fragment with biological activity against multiple drug resistance protein P-gp21 by phage display technology. Phage-displayed antibody library prepared from mice spleen tissues was selected against the recombinant protein P-gp21 with five rounds of panning. A number of clones expressing Fab bound to P-gp21, showing neutralized activity in vitro, were isolated and screened by enzyme-linked immunosorbent assay based on its recognition properties to P-gp21 and human colorectal cancer tissue homogenate, resulting in identification of an optimal recombinant Fab clone (Number 29). Further characterization by recloning number 29 into an expression vector showed significant induction of the Fab antibody in the clone number 29 by Isopropyl β-D-1-thiogalactopyranoside (IPTG). After purified by HiTrap Protein L, the specificity of the Fab antibody to P-gp21 was also confirmed. Not only was the targeted region of this monoclonal Fab antibody identified as a 16-peptide epitope (ALKDKKELEGSGKIAT) comprising residues 883–898 within the transmembrane (TM) domain of human P-gp, but also the binding ability with it was verified. The clinical implication of our results for development of personalized therapy of colorectal cancer will be further studied.